Interpersonal Communication as A Mediator of The Influence of Competence, Motivation, and Organizational Commitment on The Performance of Private University Lecturers In West Papua Province - Tekad Kurniadi Ruslak Hammar, Yunus; Mattalatta, Mattalatta; Bata Ilyas, Jamaludddin; Naninsih, Nur (Green Publisher Indonesia, 2025)
This study aims to analyze interpersonal communication as a mediator of the influence of competence, motivation and organizational commitment on the performance of private university lecturers in West Papua Province. The population of this study amounted to 263 lecturers, spread across 9 private universities. The research data was obtained from filling out questionnaires and analyzed using SEM-AMOS. The results of the study showed that: 1) competence, motivation and organizational commitment had a positive and significant effect on interpersonal communication.2) Competence, motivation and organizational commitment had a positive and significant effect on lecturer performance, 3) Interpersonal communication had a positive and significant effect on lecturer performance.4) Competence, motivation and organizational commitment had a significant effect on lecturer performance through interpersonal communication. The implication of the study is that the results of this research can be used as input and decision-making basis for PTS leaders in improving lecturer performance through increasing lecturer competence, organizational motivation and commitment as well as improving interpersonal communication of PTS lecturers in West Papua Province.